An Alternative Project for the Euston Station Area in London - Lucien Steil; John Simpson (Journal of Traditional Building, Architecture and Urbanism, 2022)
In July 2018 the University of Buckingham School of Architecture and the University of Notre Dame held a joint Architecture and Urban Design Summer Program in Central London: a four-week, full-time series of seminars, lectures, and field studies focusing on the Euston area between King’s Cross Station and Regent’s Park that will be impacted by the proposed HS2 high-speed railway terminus development. The program explored how a modern transport interchange can be accommodated within a historic city such as London in a manner that may enhance urban connectivity and serve the local community.